Challenges and Prospects of Investigative Journalism in Nigeria: A Conceptual Approach - Umeugoji Blessing Uchenna (International Journal of Humanities, Education, and Social Sciences, 2026)
Investigative journalism plays a vital role in democratic societies by exposing corruption, abuse of power, and systemic failures that threaten the public interest. In Nigeria, where governance challenges, corruption, and weak institutional accountability remain persistent, investigative journalism is both indispensable and precarious. This conceptual paper examines the challenges and prospects of investigative journalism in Nigeria through a critical synthesis of scholarly literature, relevant legal frameworks, and contemporary media-practice contexts. The analysis is guided by Social Responsibility Theory, Agenda-Setting Theory, and the Political Economy of Media to explain how structural, political, economic, legal, and professional conditions influence investigative reporting within the Nigerian media environment. The findings identify political interference, legal and regulatory repression, threats to journalists’ safety, inadequate financial and institutional resources, media ownership influence, and ineffective implementation of the Freedom of Information Act as major constraints on investigative practice. Nevertheless, the expansion of digital media, increasing public demand for accountability journalism, professional training initiatives, civil society support, and the potential for legal and institutional reforms offer important opportunities for strengthening investigative reporting. The paper concludes that the sustainability and effectiveness of investigative journalism in Nigeria depend on stronger legal protections, greater editorial independence, improved journalist safety, enhanced professional capacity, and more effective implementation of access-to-information legislation. It contributes to media and communication scholarship by integrating theoretical and contextual perspectives on investigative journalism and provides practical implications for policymakers, media organizations, professional associations, and civil society actors seeking to promote accountability, transparency, and democratic governance.